An assessment of pancreatic endocrine function and insulin sensitivity in patients with transient neonatal diabetes in remission. Issue 4 (21st June 2004) - Shield, J P H; Temple, I K; Sabin, M; Mackay, D; Robinson, D O; Betts, P R; Carson, D J; Cavé, H; Chevenne, D; Polak, M
Abstract : Aims: To examine derived indices of β cell function, peripheral insulin sensitivity, and the pancreatic response to intravenous glucose loading in children with a previous history of transient neonatal diabetes currently in remission, repeated after a period of two or more years. Methods: The standard intravenous glucose tolerance test (IVGTT) was used to measure the first phase insulin response (FPIR) cumulatively at one and three minutes. In addition, fasting insulin and glucose values were used to estimate insulinogenic indices (β cell function) and QUICKI (insulin sensitivity). Patients: Six patients with known previous transient neonatal diabetes currently in remission with no exogenous insulin requirement were tested. Control data from 15 children of a similar age were available for derived fasting indices of β cell functional capacity and insulin sensitivity. Results: One child had a subnormal insulin secretory response to intravenous glucose that remained abnormal two and four years later. The other children had relatively normal or entirely normal responses over two years. Measures of β cell function and insulin sensitivity in the fasting state showed comparable results to those obtained from normal controls. Conclusions: Most children with transient neonatal diabetes in remission have no evidence of β cell dysfunction or insulin resistance in the fasting state, although they might have been expected to show subtle defects given the tendency to relapse in adolescence. Measures of insulin response to intravenous glucose loading are often normal but suggest future recurrence if profoundly abnormal.